Patient-reported outcomes utilizing the BREAST-Q questionnaire after breast-conserving surgery with and without oncoplastic breast surgery: a systematic review and meta-analysis - Panayi, Adriana C.; Knoedler, Samuel; Knoedler, Leonard; Tapking, Christian; Hundeshagen, Gabriel; Diehm, Yannick; Fischer, Sebastian; Thamm, Oliver Christian; Kneser, Ulrich; Haug, Valentin (Aesthetic surgery journal, 2024)
Oncoplastic breast surgery (OBS) arose to decrease the deformity following breast-conserving surgery (BCS) for breast cancer. In this meta-analysis (MA), we pool BREAST-Q questionnaire data to compare quality of life (QOL) in breast cancer patients who received BCS alone or in combination with level I or II oncoplastic breast surgery (BCS + OBS). All relevant databases were searched following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and QUOROM (Quality of Reporting of Meta-Analyses) guidelines. All prospective or retrospective studies with a BCS or BCS + OBS cohort that reported QOL as assessed with the BREAST-Q questionnaire were eligible. Fifty-five studies (75 distinct patient cohorts; 11,186 patients) were included in the MA, with 12 studies reporting both preoperative and postoperative values and eligible for a pair-wise MA. The pair-wise MA showed a significant postoperative improvement in the overall satisfaction with the breast (mean difference [MD] +8.0%, P = .003) and in the psychosocial well-being (MD +9.2%, 3.5-14.8, P = .001) of the entire cohort (BCS and BCS + OBS). A subgroup MA of proportions highlighted a superiority of BCS + OBS to BCS in overall satisfaction with the breast (72.0%, 68.0-76.1, vs 62.9%, 58.3-67.5; P = .02) and psychosocial well-being (78.9%, 71.5-86.4, vs 73.3%, 67.3-76.5, P = .0001). A leave-1-out sensitivity analysis confirmed the results of the pair-wise MA and the MA of proportions. Oncoplastic breast surgery effectively improves QOL and patient satisfaction based on the patient-reported outcomes assessed with the BREAST-Q questionnaire. The improvements were associated with acceptable complication rates, further supporting BCS followed by OBS when mastectomy would otherwise be necessary.